Construction of Elementary School Students in Responding to Pros and Cons Issues (Qualitative Descriptive Study of the Functions of Discussion Texts) - Dwi Alia (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study Construction of Elementary School Students in Responding to Pros and Cons Issues (Qualitative Descriptive Study of the Functions of Discussion Texts). Critical thinking plays an important role in human daily life. Someone who has the ability to think critically can also develop other thinking skills, such as the ability to solve problems and make decisions. Critical thinking is an activity in response to a certain phenomenon that occurs due to a number of deficiencies. Critical thinking skills are important to be mastered by students, in the midst of the rapid development of science and technology, causing the sources and essence of information received by students to vary greatly. Students are required to have the ability to choose and sort out good and correct information to enrich their thinking assets (Firdaus, 2019). Another thing that is the reason is that students are one of the resources that have high potential, which must be directed with adequate thinking skills. The method used in this study is a qualitative descriptive method. The instruments used to collect data in this study were data cards with the object of research in the form of students' writings. Based on this research, it can be seen that students are able to think critically with a very simple pattern. The function of the text they build is to convince and evaluate with a direct structure to the point.